An Overview on the Forging Behaviour of Aluminum Matrix Nano Composites. (2018) - Purohit, Rajesh; Qureshi, MMU; Patil, Swapnil
Abstract: The automobile, aerospace, defense and recreation industries need a material having good mechanical properties like high tensile strength, high toughness, hardness along with light weight i.e. with high strength to weight ratio and the aluminum alloys reinforced with ceramic particles have opened up a wide range of solutions. For last two decades the research in composite materials has been shifted toward nano particle reinforcement because of their several advantages. This paper reviews the recent studies on the effect of forging on properties of aluminum matrix nano-composites. The forging process results in aligned grain flow pattern and with fibrous structure and improvement in properties.